Tren penelitian dan tantangan penerapan Common European Framework of Reference for Languages (CEFR) di Indonesia - Robbani, A. Syahid; Nurdianto, Talqis; Annafiri, Ahmad Zaki; Haqqy, Ahmad Muzayyan; Irfan, Irfan (Universitas Mulawarman, 2023)
The Common European Framework of Reference for Languages (CEFR) in language learning is incredibly beneficial to language learners, language teachers, and educational institutions. However, the implementation of CEFR does not appear to be comprehensive, one of which is due to the weakness empirical research on CEFR and various other factors. Therefore, this research aims to provide a comprehensive information regarding the extent to which CEFR studies in Indonesia have been carried out and various challenges in implementing CEFR in Indonesia. This research is a systematic review with the object of study are articles published in scientific journals during 2011—2021. This systematic review found surprising results where from 2011-2015, there was not found a single study on CEFR in Indonesia. The peak of articles publication on CEFR in Indonesia occurred in 2020, with a total publication of 15 articles. Other findings show that English is the dominant target language in CEFR studies in Indonesia. The challenges and problems of implementing CEFR in Indonesia are generally divided into three, challenges and problems related to educational institutions, teachers and CEFR itself.